Negociações coletivas e indústria 4.0 na EU-15: uma análise de modelos condicionais mistos - Dutra, Matheus Henrique de Araújo (2023)
Industry 4.0, understood as an innovation process based on cyber-physical systems and the "Internet of Things", is raising the interest of the scientific community for its disruptive potential and its economic and world of work impacts. Thereof, this dissertation aims to analyze the relationship between collective agreements and Industry 4.0 companies in 15 countries of the European Union, based on the level at which they occur and the different industrial relations of different groups of countries, using the concept of Varieties of Capitalism as a theoretical basis. Thus, biprobit-type models are estimated to verify the probability that a bussiness company uses or introduces technologies related to Industry 4.0, based on the level at which such negotiations are presented in a set of explanatory variables from a sample of the European Company Survey. Given the possible presence of unobserved endogeneity and heterogeneity problems, the models are estimated using the estimator of Deb and Trivedi (2006b). The results indicate a positive and significant relationship between the presence of collective agreements, especially that occurring at higher levels, and the probability that the company introduces or already uses I.4.0 technologies. It is also found that collective agreements has a non-linear effect on innovation, and this impact is more relevant in companies with a lower tendency to innovate, belonging to liberal market economies.